2015
DOI: 10.1128/jvi.00013-15
|View full text |Cite
|
Sign up to set email alerts
|

The Nuclear DNA Sensor IFI16 Acts as a Restriction Factor for Human Papillomavirus Replication through Epigenetic Modifications of the Viral Promoters

Abstract: The human interferon-inducible IFI16 protein, an innate immune sensor of intracellular DNA, was recently demonstrated to act as a restriction factor for human cytomegalovirus (HCMV) and herpes simplex virus 1 (HSV-1) infection by inhibiting both viral-DNA replication and transcription. Through the use of two distinct cellular models, this study provides strong evidence in support of the notion that IFI16 can also restrict human papillomavirus 18 (HPV18) replication. In the first model, an immortalized keratino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
97
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 87 publications
(104 citation statements)
references
References 65 publications
(99 reference statements)
5
97
0
Order By: Relevance
“…The antiviral function of IFI16 can be subdivided into two distinct mechanisms: (i) an immune surveillance role, where IFI16 activates the inflammasome and IFN-␤ pathways in response to foreign viral DNA in the nucleus (28,34,38,40,73,77,78), and (ii) a gene regulatory role, where it transcriptionally represses viral transcription and replication (29,37,39,79). So far, this gene regulatory role of IFI16 has been demonstrated for HSV-1, HCMV, and HPV (29,36,37,39). In these viruses, IFI16 has been shown to either epigenetically modify the viral chromatin so as to favor heterochromatin marks or alter the binding of transcription factors on the viral promoters.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The antiviral function of IFI16 can be subdivided into two distinct mechanisms: (i) an immune surveillance role, where IFI16 activates the inflammasome and IFN-␤ pathways in response to foreign viral DNA in the nucleus (28,34,38,40,73,77,78), and (ii) a gene regulatory role, where it transcriptionally represses viral transcription and replication (29,37,39,79). So far, this gene regulatory role of IFI16 has been demonstrated for HSV-1, HCMV, and HPV (29,36,37,39). In these viruses, IFI16 has been shown to either epigenetically modify the viral chromatin so as to favor heterochromatin marks or alter the binding of transcription factors on the viral promoters.…”
Section: Discussionmentioning
confidence: 99%
“…IFI16 is a multifunctional DNA binding protein and has been implicated in various cellular functions such as transcriptional regulation, apoptosis, autoimmunity, and cell cycle regulation (25)(26)(27). Studies by us and others have reported the role of IFI16 as a DNA sensor that detects nuclear replicating herpesviral genomes such as KSHV, herpes simplex virus 1 (HSV-1), EpsteinBarr virus (EBV), and bovine herpesvirus 1 (BoHV-1), leading to IFI16 -apoptosis-associated speck-like protein containing a CARD (ASC)-procaspase-1 inflammasome formation that results in the production of the inflammatory cytokine interleukin 1␤ (IL-1␤) (28)(29)(30)(31)(32)(33). We have also shown that IFI16-mediated inflammasomes are activated during prolonged KSHV latency in endothelial and B cells, leading to a constitutive state of IL-1␤ activation (34).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The chromatin immunoprecipitation (ChIP) assay was performed as previously described (39). Briefly, HFFs were infected with v65Rev or v65Stop at an MOI of 1 for 6 h and 36 h. ChIP assays were performed using the shearing optimization kit and the OneDay ChIP kit (Diagenode Europe).…”
Section: Cells and Virusesmentioning
confidence: 99%
“…IFI16 has been implicated in the initiation of DNA virus-induced inflammasome signaling (5)(6)(7)(8), the transcription of antiviral cytokines and interferon-stimulated genes (ISGs) (9)(10)(11), and the restriction of DNA virus replication (12)(13)(14)(15)(16). The importance of IFI16 in antiviral immunity is underscored by the identification of viral proteins that inhibit its antiviral activities.…”
mentioning
confidence: 99%